Assessing the immune response to SARS-CoV-2 mRNA vaccines in siponimod-treated patients: a nonrandomized controlled clinical trial (AMA-VACC) - Tjalf Ziemssen; Marie Groth; Benedict Rauser; Tobias Bopp (Therapeutic Advances in Neurological Disorders, 2022)
Background: Systematic data are lacking on the immune response toward SARS-CoV-2 mRNA vaccination in SPMS patients on disease-modifying therapies (DMTs). Objective: The AMA-VACC clinical trial was designed to characterize immune responses to SARS-CoV-2 mRNA vaccines in siponimod-treated SPMS patients. Design: AMA-VACC is an ongoing three-cohort, multicenter, open-label, prospective clinical study. Methods: The study included patients at risk for SPMS or patients with SPMS diagnosis. Patients received SARS-CoV-2 mRNA vaccine as part of their clinical routine during ongoing siponimod treatment (cohort 1), during siponimod treatment interruption (cohort 2), or while on dimethyl fumarate, glatiramer acetate, beta-interferons, teriflunomide, or no current therapy (cohort 3). SARS-CoV-2-specific neutralizing antibodies and T-cell responses were measured 1 week and 1 month after the second dose of vaccination. Results: In total, 17 patients, 4 patients, and 20 patients were recruited into cohorts 1, 2, and 3, respectively. The primary endpoint of seroconversion for SARS-CoV-2-neutralizing antibodies at week 1 was reached by 52.9%, 75.0%, and 90.0% of patients in cohorts 1, 2, and 3, respectively. For 64.7% of patients in cohort 1, all patients in cohort 2, and 95% of patients in cohort 3, seroconversion was observed at either week 1 or month 1 or both time points. After 1 week, 71.4% of cohort 1, 75.0% of cohort 2, and 85.0% of cohort 3 were positive for either SARS-CoV-2-neutralizing antibodies or SARS-CoV-2-specific T-cells or both. After 1 month, the rates were 56.3%, 100.0%, and 95.0%, respectively. Conclusion: The study shows that the majority of siponimod patients mount humoral and cellular immune response under continuous siponimod treatment. The data do not sufficiently support interruption of treatment for the purpose of vaccination. Registration: EU Clinical Trials Register: EudraCT 2020-005752-38 ( www.clinicaltrialsregister.eu ); ClinicalTrials.gov: NCT04792567 ( https://clinicaltrials.gov ).